Invariant Point Results in Complete Soft S-Metric Spaces for Rational Expression - et. al, Sneha A. Khandait (International Journal of Advanced Science and Technology, 2020)
In this paper, the notion of soft S-metric spaces is introduced. The soft S-metric space via soft element is defined. Some common fixed point theorems for compatible and weakly compatible mapping in soft S-metric spaces are established. The derived results which is generalized form of some previous well known results from S-metric spaces.